n would equal <em>-33</em>.
<em>n=-33</em>
<h2>f = -5</h2><h3></h3><h3>f(x) = 4x - 9</h3><h3>Add 9 to both sides</h3><h3>f(x) + 9 = 4x</h3><h3>Divide x from both sides</h3><h3>f + 9 = 4</h3><h3>Subtract 9 from both sides</h3><h3>f = -5</h3><h3></h3><h3><em>Please let me know if I am wrong.</em></h3>
Your answer would be -35.
Answer:
(x+3)( 3x^2 +5)
Step-by-step explanation:
3x^3+9x^2+5x+15
Split into two groups
3x^3+9x^2 +5x+15
Factor 3x^2 out of the first group and 5 out of the second group
3x^2 ( x+3) + 5(x+3)
Factor out x+3
(x+3)( 3x^2 +5)